We will rest! : the art of escape - Hersey, Tricia (Rest is resistance, 2024)
"...a modern sacred object, medicine for a sick and exhausted world. Weaving together meditations and poetry with storytelling and art, Hersey provokes liberation through refusal and trickster rebellion in the face of capitalism and white supremacy. Focus on the escape. Focus on the transformation. We can just be. We are beautiful. We are enough. We are escape artists. We Will Rest!"--